A method for the production and expedient screening of CRISPR/Cas9-mediated non-transgenic mutant plants. Issue 1 (2nd March 2018) - Chen, Longzheng; Li, Wei; Katin-Grazzini, Lorenzo; Ding, Jing; Gu, Xianbin; Li, Yanjun; Gu, Tingting; Wang, Ren; Lin, Xinchun; Deng, Ziniu; McAvoy, Richard J; Gmitter, Frederick G; et al.
Abstract: Developing CRISPR/Cas9-mediated non-transgenic mutants in asexually propagated perennial crop plants is challenging but highly desirable. Here, we report a highly useful method using an Agrobacterium -mediated transient CRISPR/Cas9 gene expression system to create non-transgenic mutant plants without the need for sexual segregation. We have also developed a rapid, cost-effective, and high-throughput mutant screening protocol based on Illumina sequencing followed by high-resolution melting (HRM) analysis. Using tetraploid tobacco as a model species and the phytoene desaturase ( PDS ) gene as a target, we successfully created and expediently identified mutant plants, which were verified as tetra-allelic mutants. We produced pds mutant shoots at a rate of 47.5% from tobacco leaf explants, without the use of antibiotic selection. Among these pds plants, 17.2% were confirmed to be non-transgenic, for an overall non-transgenic mutation rate of 8.2%. Our method is reliable and effective in creating non-transgenic mutant plants without the need to segregate out transgenes through sexual reproduction. This method should be applicable to many economically important, heterozygous, perennial crop species that are more difficult to regenerate. Crop breeding: A new technique for using CRISPR/Cas9 to create non-transgenic mutant crop plants: A group led by Dr. Yi Li of University of Connecticut, USA has developed a technique to reliably create desirable mutations in crop plants without introducing any foreign DNA, thus generating non-transgenic mutant plants. Their technique will be particularly important for application of genome editing technologies in perennial crop plants. Genome editing technologies have been used to introduce desired mutations into plants but the approach normally incorporates foreign genes such as Cas9 into the plant's genome. To avoid this, Dr. Li's team has used Agrobacterium to transiently express the CRISPR/Cas9 components, a bacterium commonly used to genetically engineer plants. With their method, CRISPR/Cas9 from the bacteria edit the plant genome without introducing any foreign DNA, and then a two-step screening process is used to identify non-transgenic mutant plants. This new method provides a reliable and efficient alternative for producing non-transgenic genetically engineered crops.